From Dialogue to Engagement: Experiences of Civil Society Organizations in Religious Literacy Programs for Multicultural Education Curriculum in Indonesia - M. Amin Abdullah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – The purpose of this research is to learn about civil society organizations' experiences in cross-cultural religious literacy programs and what should be done to maintain harmonious, non-conflictual relations between people of different religions and beliefs Design/methods/approach – This study was conducted to explore in-depth information about the experiences of civil society organizations (CSOs) in cross-cultural religious literacy programs. One of the CSOs in Indonesia mentioned in this research is the Leimena Institute, which shares its experience in various literacy activities, including cross-cultural literacy. The purpose of this study is to learn about the experience of civil society organizations in cross-cultural religious literacy programs, not to mention to find out what should be done to maintain harmonious-non-conflictual relations between people of religion and belief. The data for this qualitative research was taken from related documents. Findings – There are international interfaith documents that speak of the importance of building togetherness in organizing life for the better. The dialog process is one of the efforts that can be carried out to allow the spread of the spirit of cross-cultural religious literacy, to bring up a multicultural-multireligious education curriculum. Research implications/limitations – This research has theoretical and ideological implications for producing educational innovation. The efforts made by the Islamic community and the international community have a positive impact on efforts to build a broad educational network. As a result, the predictions of future education that is multicultural and multireligious will be able to be faced calmly and fully prepared Originality/value – This research illustrates how dialogues will build good engagement and produce significant changes in the world of education towards a multicultural-multireligious future education